2018
DOI: 10.1007/s00429-018-1811-1
|View full text |Cite
|
Sign up to set email alerts
|

Gradients of connectivity distance in the cerebral cortex of the macaque monkey

Abstract: Cortical connectivity conforms to a series of organizing principles that are common across species. Spatial proximity, similar cortical type, and similar connectional profile all constitute factors for determining the connectivity between cortical regions. We previously demonstrated another principle of connectivity that is closely related to the spatial layout of the cerebral cortex. Using functional connectivity from resting-state fMRI in the human cortex, we found that the further a region is located from p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 68 publications
7
35
0
Order By: Relevance
“…This is in line with a previous study that used a similar approach (39). It is further in line with organizing principles of the brain that regions tend to be more interconnected when they are located close to each other (40,41). However, when we compared the regions loading on the two components, the covarying regions of each component distribute in different brain locations.…”
Section: Discussionsupporting
confidence: 89%
“…This is in line with a previous study that used a similar approach (39). It is further in line with organizing principles of the brain that regions tend to be more interconnected when they are located close to each other (40,41). However, when we compared the regions loading on the two components, the covarying regions of each component distribute in different brain locations.…”
Section: Discussionsupporting
confidence: 89%
“…The functional affinity matrix was built using the same steps described by 23 . In reporting the results we explicitly looked for gradients capturing the polymodal-unimodal differentiation as well as the modality specific organization of cortical connectivity as described in recent human and primate work 23,64 . In line with human results, we found that the dominant gradient of both SC and FC recapitulates the unimodal-polymodal continuum (Gradient A in Figure 5A and 5B), whereas the second ranked functional and the third ranked structural gradients delineate comparable modality specific spatial configuration of cortical connectivity (Gradient B).…”
Section: Functional and Structural Gradientsmentioning
confidence: 99%
“…Degree centrality is defined as the row-wise sum of the weighted connectivity matrix, representing the connection strength of a given node 70 . Connectivity distance is a given brain region's geodesic distance to its structurally connected brain areas within the cortex 134 , and it is defined as the multiplication between the geodesic distance and the binarized structural connectome 10,134 . Within-module degree and participation coefficient are nodal measures reflecting different facets of community organization 70,[135][136][137] .…”
Section: Association With Connectome Topologymentioning
confidence: 99%